Pengaruh Kebijakan dan Faktor Penentu Impor Bawang Putih Indonesia dari Cina - Jihan Zakia Adila; Andriyono Kilat Adhi; Rita Nurmalina (Jurnal Penelitian Pertanian Terapan, 2022)
The government has targeted garlic self-sufficiency in 2021 to meet the national demand for garlic. However, most of Indonesia's garlic needs are still met by importing garlic from garlic-producing countries. This study aims to analyze the influence of policies and determinants of Indonesian garlic imports from China as the largest garlic exporter in Indonesia and globally. This study analyzes the annual time series data from 1996 to 2019 using multiple linear regression with the Ordinary Least Square (OLS) method. This study found that the tariff elimination policy significantly affected the volume of garlic imports from China. Imported garlic prices, Indonesian population, and domestic shallot prices also significantly affect the volume of Indonesian garlic imports from China. Meanwhile, the RIPH policy and the real exchange rate did not significantly affect Indonesia's garlic imports from China.